Gangguan pertumbuhan sebagai komplikasi talasemia • mayor - Nur Robbiyah; Hakimi dr; Melda Deliana; Siska Mayasari (Fakultas Kedokteran USU, 2014)
Beta-thalassemias major are a group of hereditary blood disorders disease. Growth disorders are afrequent complication of patient with Beta-thalassemias major. The pathogenesis of disorders is multifactorial and is mainly due to chronic anemia and hypoxia, chronic liver disease, zinc and folic acid deficiency, iron overload and intensive use of chelating agents. Proper management of each patient with beta-thalassemias major include early recognition of growth disorders and appropriate of iron chelation therapy is very important to improve the quality of life.Keywords : beta-thalassemias major; growth disorders